Determinants of trust in times of crises: A cross-sectional study of 3,065 German-speaking adults from the D-A-CH region. - Eva S Schernhammer; Jakob Weitzer; Emilie Han; Martin Bertau; Lukas Zenk; Guido Caniglia; Manfred D Laubichler; Brenda M Birmann; Gerald Steiner (PLoS ONE, 2023)
Interpersonal trust declined worldwide during the COVID-19 pandemic; strategies are needed to restore it. We surveyed 3,065 quota-sampled German-speaking adults residing in the D-A-CH region. Using multinomial logistic regression models and backward elimination for variable selection, we calculated multivariable-adjusted odds ratios (OR) and 95% confidence intervals (95% CIs) to appraise correlates of interpersonal trust using the Interpersonal Trust Short Scale (KUSIV3). Participants with high levels of interpersonal trust (top KUSIV3 tertile (T3)) tended to be older, male, residents of Switzerland, university degree holders, and workers with higher income and work satisfaction (all Pdiff<0.01) compared to those in the lowest KUSIV3 tertile (T1). Optimism was most strongly associated with high interpersonal trust (ORT3vsT1 = 5.75, 95%CI = 4.33-7.64). Also significantly associated with high interpersonal trust were: Having voted in the last national election (for the opposition, OR = 1.39, 95%CI = 1.02-1.89 or the governing party, OR = 1.61, 95%CI = 1.23-2.11) versus non-voters; perspective taking (ORT3vsT1 = 1.46, 95%CI = 1.11-1.91); being more extraverted (ORT3vsT1 = 1.99, 95%CI = 1.53-2.59) and more agreeable (ORT3vsT1 = 1.95, 95% CI = 1.46-2.61); and scoring higher on complexity thinking (ORT3vsT1 = 1.32, 95%CI = 1.01-1.72). Participants scoring significantly lower for interpersonal trust did not regularly participate in religious meetings (OR = 0.61, 95%CI = 0.44-0.84, versus participation at least monthly); were more conscientious (ORT3vsT1 = 0.68, 95%CI = 0.51-0.91) or current smokers (OR = 0.68; 95%CI = 0.53-0.87, versus never smoking); had sleep problems >5 times a week (OR = 0.48; 95%CI = 0.36-0.66, versus none); and scored high on conspiracy belief (ORT3vsT1 = 0.53; 95%CI = 0.41-0.69). Results differed minimally by gender and country. These findings may be helpful in devising targeted strategies to strengthen interpersonal trust and social engagement in European societies, especially during times of crises.